Impact of the SARS-CoV-2 on the journey of high-risk colon cancer patients within the scope of the Unified Health System in Brazil - Raquel Pucci de Oliveira; Pedro Henrique Rezende de Moraes; Ana Paula Drummond-Lage (BMC, 2023)
Abstract Background Colon cancer is an important cause of mortality related to cancer. During the COVID-19 pandemic, an important reallotment of assistance resources was necessary to tackle the crisis, directly impacting medical practice all over the globe. Objective To assess the impact of the Sars-Cov-2 pandemic on the time between diagnosis and the beginning of systemic treatment in patients diagnosed with high-risk colon neoplasia. Methods This is a retrospective study based on the analysis of medical records of patients diagnosed with colon neoplasia who required systemic treatment and were treated between March 2019 and March 2022, in a reference Oncology unit of the Brazilian Unified Health System. The study's population was divided into two groups: (I) Pre-COVID-19: diagnoses made between March 2019 and February 2020, (II) COVID-19: diagnoses made between March 2020 and March 2022. Results The sample consisted of 228 patients, 108 (47.97%) of whom were diagnosed during pre-COVID-19 and 118 (52.21%) diagnosed during the two years-period of COVID-19. Regarding the time between colonoscopy and surgery, the time between surgery and first consultation in clinical oncology, and the time between requesting and beginning of systemic treatment, a statistically significant reduction was observed during the COVID-19 period. Conclusion A decrease in time between diagnosis and systemic treatment of patients with colorectal cancer during the COVID-19 pandemic was observed. Yet, even with this improvement, the time to begin treatment remains greater than the recommended by the current guidelines, regardless of the time of diagnosis (before or after the pandemic), which negatively impacts the disease outcome.